Linux administration : a beginner's guide - Soyinka, Wale (Online access with DDA: Askews (Maths), 2016)
Now with a downloadable virtual machine showcasing the book's test system configuration and updated for the latest Linux kernel release, the new edition of this bestseller teaches system administrators how to set up and configure Linux quickly and easily.